2018
DOI: 10.1016/j.foodchem.2018.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in Hibiscus sabdariffa (Roselle) calyx phytochemical profile, soluble solids and α-glucosidase inhibition

Abstract: Seasonal variations in crops can alter the profile and amount of constituent compounds and consequentially any biological activity. Differences in phytochemical profile, total phenolic content and inhibitory activity on α-glucosidase (maltase) of Hibiscus sabdariffa calyces grown in South Western Nigeria were determined over wet and dry seasons. The phenolic profile, organic acids and sugars were analysed using HPLC, while inhibition of rat intestinal maltase was measured enzymically. There was a significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 25 publications
3
24
6
2
Order By: Relevance
“…As described by other authors (Ifie, Ifie, Ibitoye, Marshall, & Williamson, 2018;Jabeur et al, 2017;Sindi, Marshall, & Morgan, 2014), C1 predominated over C2 in all cases (Table 2), with levels ranging from 1,02-6.88 mg/g P and 0.43-2.11 mg/g P for HAE and from 1.26 to 14.31 mg/g P and 0.92-7.29 mg/g P for UAE, respectively. The highest total content (CT) was achieved with the runs 13 (8.99 mg/ g P) and 10 (21.48 mg/g P) of the HAE and UAE processes, respectively.…”
Section: Experimental Data For Rsm Optimizationsupporting
confidence: 80%
See 1 more Smart Citation
“…As described by other authors (Ifie, Ifie, Ibitoye, Marshall, & Williamson, 2018;Jabeur et al, 2017;Sindi, Marshall, & Morgan, 2014), C1 predominated over C2 in all cases (Table 2), with levels ranging from 1,02-6.88 mg/g P and 0.43-2.11 mg/g P for HAE and from 1.26 to 14.31 mg/g P and 0.92-7.29 mg/g P for UAE, respectively. The highest total content (CT) was achieved with the runs 13 (8.99 mg/ g P) and 10 (21.48 mg/g P) of the HAE and UAE processes, respectively.…”
Section: Experimental Data For Rsm Optimizationsupporting
confidence: 80%
“…Beye et al (2017) recovered up to 9.19 mg C1/g P and 4.72 mg C2/g P from dried calyces of H. sabdariffa cultivars grown in Senegal, when subjected to a 60-min extraction with acetone followed by five more 60min extraction cycles with acetone/acidified water (70:30, v/v; 4% formic acid). Higher levels of C1 (up to 21.2 mg/g P), but lower of C2 (up to 5.17 mg/g P) were obtained by Ifie et al (2018) in dried calyces of a dark red variety of H. sabdariffa cultivated in Ibadan, South-Western Nigeria, in comparison with the quantities found in our samples harvested in north-eastern Portugal. These contents were obtained by three successive aqueous extractions of 30-min duration at 50°C.…”
Section: Experimental Data For Rsm Optimizationcontrasting
confidence: 63%
“…According to some authors, exposure to water stress causes an increase in sugar content in some fruit and vegetables. Specifically, a study with H. sabdariffa calyces proved the effect of seasonal variation in organic acids and sugars, demonstrating that in general the content of sugars and organic acids were higher during the dry season 20 . Therefore, these considerations could be taken into account to justify the observed differences found between the samples.…”
Section: Nutritional and Chemical Characterizationmentioning
confidence: 96%
“…Plants are daily subject to several external factors that can cause changes in their composition and bioactive activities. Different studies regarding the effects of drought and osmotic stress on the polyphenols composition in distinct species have demonstrated that these compounds could increase or decrease (depending on the species), with the type and intensity of stress 20 .…”
Section: Nutritional and Chemical Characterizationmentioning
confidence: 99%
“…Variation of up to 70% in the contents of total soluble phenolic compounds and anthocyanins according to the production site has been reported [9]. In addition, the authors of [21] demonstrated that drought stress during roselle cultivation increases the anthocyanin content of the calyx by up to 28%. However, it is unknown whether this effect on plant quality persists at different levels of drought and in different cultivars in commercial production.…”
Section: Introductionmentioning
confidence: 99%